The Effect of Exercise on Peer Relationship and Peer Bullying Level in Children - İhsan Kuyulu and Enes Beltekin and Tarık İnce and Mehmet Şerif Ökmen and Mehmet Sarikaya and Mustafa Türkmen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study aimed to explore the relationship between peer relations and peer bullying among children engaged in sports activities, as well as the impact of being bullied on the perpetration of bullying behaviours. The research involved 227 students, aged 13 and 14, enrolled in public schools under the Bingol Provincial Directorate of National Education. Data were collected using a questionnaire technique, specifically employing the “Peer Relationship Scale” and the “Peer Bullying Scale.” The analysis of the data was conducted using SPSS Statistics 22. Descriptive statistics, including arithmetic means, standard deviations, frequencies, and percentage distributions, were utilized to summarize demographic information and responses to group-related questions. To assess the peer relations and peer bullying levels of the participants, numerical ratios, percentage frequencies, and arithmetic mean values were calculated and presented in tabular form. Correlation analysis (Pearson) was employed to examine the relationships between the sub-dimensions of peer relations and those of bullying and being bullied. Additionally, regression analysis was performed to investigate the extent to which being bullied by peer’s influences subsequent bullying behaviour. The findings indicated that the peer relationship levels of students participating in sports activities were generally favourable. However, the levels of peer bullying and experiences of being bullied were found to be significantly high. Furthermore, it was concluded that students' engagement in bullying behaviours was influenced by prior experiences of being bullied themselves.